Optimizing General Clinic Workflows: A Systematic Review of Process Improvement Approaches - Al-Mansour , Fahad Mohammed Saed; Alsharyah, Rashed Mahdi; Al Mansour, Ibrahim Hadi; Al Mansour, Hadi Hassan Mahmoud; Hatem, Hatem Mohammed; Almansour , Saeed Hamad Saeed; Al Mansour , Mana Mahdi Ali; Almansour, Hamad Ali Suaydan; Alyami , Hussain Ali Hussain; Alyami, Hamad Hussain (Journal of Ecohumanism, 2024)
This systematic review explores process improvement approaches in general clinics, focusing on methodologies that enhance workflow efficiency, reduce patient wait times, and optimize resource utilization. By analyzing studies published between 2016 and 2024, this review identifies key interventions, including Lean, Six Sigma, workflow automation, patient-centered redesign, and AI-driven predictive analytics. Findings indicate that these approaches contribute significantly to operational efficiency, staff productivity, and patient satisfaction. However, challenges such as staff resistance, high implementation costs, and the lack of standardization remain barriers to widespread adoption. The review highlights the need for further research on integrating digital transformation with traditional process improvement models to create sustainable and scalable solutions for general clinics.